The culture wars of the late Renaissance : skeptics, libertines, and opera - Muir, Edward, 1946- (Bernard Berenson lectures on the Italian Renaissance., 2007)
In this book, Muir explores an era of cultural innovation that promoted free inquiry in the face of philosophical and theological orthodoxy, advocated libertine morals, critiqued the tyranny of aristocratic fathers over their daughters, and expanded the theatrical potential of grand opera. In so doing, he reveals the distinguished past of today's culture wars, including debates about the place of women in society, the clash between science and faith, and the power of the arts to stir emotions.